Polimorfismo T102C do gene do receptor de serotonina (5-HT2A) na suscetibilidade à fibromialgia: meta-análise - Peres, Paula Aparecida Borges (2012)
Despite its obscure aetiopathology, fibromyalgia is defined by diffuse musculoskeletal pain and not joint, and heightened sensitivity to palpation of certain muscle points, mainly affecting women, in a ratio of 6 to 10 women for every man. Several studies have demonstrated the role of polymorphisms of genes serotonergic, dopaminergic and catecholaminergic in the etiology of fibromyalgia. Thus, genetic factors may be determinants in the pathogenesis of fibromyalgia and some environmental factors may trigger fibromyalgia in genetically predisposed individuals. In this context, it seems that the gene polymorphism T102C serotonin receptor (5-HT2A) is relevant in susceptibility to fibromyalgia. The objective of this study was to perform a metaanalysis in order to investigate the association between polymorphism of the serotonin receptor gene (5-HT2A), the T102C SNP in susceptibility to fibromyalgia. Five studies, between the years 1999 to 2011, about 5-HT2AT102C polymorphism in fibromyalgia were selected and used for making a meta-analysis. The epidemiological profile of fibromyalgia patients revealed a mean age of 46.7 (+ 5.9) years, with extremes ranging from 21 to 77 years. The proportion between genders showed a difference of approximately 7 women for every man diagnosed fibromyalgia. The average time in which patients suffering from fibromyalgia syndrome is 7.4 (+ 2.9) years. Allele frequencies for T and C, the gene for 5- HT2AT102C were, respectively, for patients: 337 (43.1%) and 445 (56.9%) and for the controls: 362 (51.6%) and 340 (48.4%), indicating a predominance of the C allele in patients with fibromyalgia (p=0.0013). When evaluating the genotypic frequencies, we found: 73 (18.7%) TT, 191 (48.8%) and TC 127 (32.5%) CC. The control group: 98 (27.9%) TT, 166 (47.3%) and TC 87 (24.8%) CC. The CC genotype appears more frequently in the patients fibromyalgia patients (p=0.0046). A meta-analysis generated a universe of simultaneous evaluation of 742 individuals (391 fibromyalgia patients and 351 controls). The applied tests indicated no significant differences between the case and control groups. Thus, the result of the meta-analysis suggests no correlation between polymorphism in question and susceptibility to fibromyalgia. We suggest the use of a broad panel of SNPs with the intention of increasing the chances of finding an association between genetic polymorphisms and susceptibility to fibromyalgia.